Microsoft Outlook Bagi Pemula - Indah Pratwi; Sabrina Nasution; Ahmad Khoiri; Rizki Fadillah Yoga; Nurbaiti Nurbaiti (Universitas Muhammadiyah Enrekang, 2022)
This study aims to provide knowledge to new users about Microsoft Outlook which will make their work easier. This method is used to describe and explain Microsoft Outlook in written form taken from several studies and literature. The purpose of this research is to introduce Microsoft Outlook for beginners. Ms Outlook has several other functions that you can apply, the first is starting from making a work schedule, then there is a calendar, also notes, and journals to make all work easier. With the Microfost Exchange Server or SharePoint, Microsoft Outlook is able to access mailboxes, calendars, data aggregations, folders, and scheduled meetings such as meetings. Microsoft Outlook is a personal information management program whose job is to help manage time and information more effectively, efficiently and enable users to share information more easily. Microsoft Outlook is part of the Microsoft Office suite that has standalone applications and is also part of the Microsoft Office suite. Microsoft Personal Information Manager.